A random access algorithm for LTE systems. Issue 1 (12th September 2012) - Sanguinetti, L.; Morelli, M.; Marchetti, L.; Dammann, Armin; Plass, Simon; Fazel, Khaled
ABSTRACT The random access procedure is a contention‐based synchronisation process specified by long‐term evolution standards by which uplink signals can arrive at the eNodeB synchronously and with approximately the same power level. In this work, a novel random access algorithm for initial synchronisation in long‐term evolution systems is derived on the basis of a generalised likelihood ratio test. In contrast to existing methods, our approach provides better results by properly taking into account the frequency selectivity of the channel. This is achieved at the price of an increase of the system complexity. Computer simulations are employed to assess the effectiveness of the proposed solution and to make comparisons with existing alternatives. Copyright © 2012 John Wiley & Sons, Ltd.